Food Bank Mobile Application (Share Pantry) - Afifah Nabilah, Mohd Suhaimi (2023)
Nowadays, the usage of mobile technology has become a trend in a huge area such as education, entertainment, online business, and other kinds of areas that gives benefits. There are various applications that can benefit the community. Mobile applications enable new ways of working in an increasingly connected and mobile world. Enterprises realize the advantages and are gearing up to get ahead. With the increasing numbers of mobile applications being deployed, it is important for organizations to make the most efficient investments for their enterprise mobility needs. Mobile development platforms with multi-channel deployment capabilities, security, management, and back-end integration capabilities make a whole lot of sense. Besides, mobile applications allow fast and effective data management through internetwork facilities. The mobile application for food bank is developed for people who need help from food bank, people who want to make donation, people who want to be volunteer to help distribute the food bank, and for NGO itself. They can make donations or make requests for food banks remotely from different locations. These users will help to spread the food bank information via mobile devices. In the meantime, some NGOs are still using old-fashioned ways in taking data of donors, needed people and volunteers. Some situations are only known by NGO and not to the community. So, the aim of this project is to provide food bank services to users and provide locations of nearby food bank in entire Malaysia using GPS and Google Map graphical user interface. As a result, users can easily identify available and nearby food banks and make donations or requests. This application is much faster and can be used in anytime and anywhere as long as there is an internet connection.